Picasso Guerica - Harrison, Miranda; Sofia, Reina (London Scala, 2003)
fold format is ideal for exploring this fascinating painting. Divided into thematic sections, it takes the reader through each aspect of the painting, showing preliminary sketches, repeated themes in Picasso's work and dramatic aerial shots of the bombing of Guernica, culminating in a splendid horizontal fold-out of the entire painting. The Series Scala are
Keywords: Picasso; Painting -- 17th and 18th centuries; Pictures